Long-term performance of homografts versus stented bioprosthetic valves in the pulmonary position in patients aged 10–20 years. (11th April 2018) - Bell, Douglas; Prabhu, Sudesh; Betts, Kim S; Chen, Yilin; Radford, Dorothy; Whight, Chris; Ward, Cameron; Jalali, Homayoun; Venugopal, Prem; Alphonso, Nelson
Abstract: OBJECTIVES: We aimed to compare the long-term performance of pulmonary homografts and stented bioprosthetic valves in the pulmonary position in patients aged 10–20 years. METHODS: Between January 1995 and December 2015, 188 patients aged 10–20 years undergoing pulmonary valve replacement were identified retrospectively from hospital databases in both congenital cardiac centres in Brisbane. Valve performance was evaluated using previously described standard criteria. Propensity score matching was used to balance the 2 treatment groups. RESULTS: Freedom from structural valve degeneration in homografts ( n = 131) was 97%, 92% and 85% at 3, 5 and 10 years, respectively, and 91% and 53% at 3 and 5 years, respectively, in the bioprosthesis group ( n = 57). Freedom from reintervention in homografts was 96%, 93% and 88% at 3, 5 and 10 years, respectively, and 93% and 68% at 3 and 5 years, respectively, in the bioprosthesis group. The unadjusted Cox regression analysis demonstrated that a bioprosthesis was at 5.64 times the risk of structural valve degeneration and 3.89 times the risk of reintervention. The Cox regression analysis performed on the propensity matched sample (45 pairs of patients) revealed that a bioprosthesis was at almost 10 times the risk of experiencing structural valve degeneration [hazard ratio (HR) = 9.18] and at more than 8 times the risk of undergoing a reintervention (HR = 8.34). CONCLUSIONS: In our patient population, pulmonary homografts outperformed stented bioprosthetic valves within 5 years when implanted in the pulmonary position in patients aged 10–20 years. We recommend the use of a pulmonary homograft for pulmonary valve replacement in this age group in patients undergoing surgery for congenital heart disease.